Correlación Mastográfica E Histopatológica En Lesiones De Mama No Palpables - Ma. Azucena, Bello-Sánchez; Enrique, Villarreal-Ríos; Leticia, Blanco-Castillo; Manuel, Medina-Carreón; Danae, Reyes-Chávez Prishila; Leticia, Martínez-Martínez Martha; Nicolás, Camacho-Calderón (European Scientific Journal, ESJ, 2016)
Globally, breast cancer ranks first in malignancies. It affects women over 40 years. An early diagnosis of no-palpable lesions, in sub-clinical stages, increases the probability of detecting at an early stage with increase survival and disease-free interval. Objective: To determine the correlation between mammography and histopatological lesions non palpable breast. Material and Methods: Study with correlational design. Histopathological records in women with non-palpable lesions and mamography of the Mexican Social Security Institute, Querétaro, Mexico from 2011-2013. Sample size for correlational studies. Data obtained from the medical records of women with mammography BI-RADS 2 to 5 and confirmatory histopathology. Variables analized: sociodemographic data, family history of breast cáncer, histopathological diagnosis and mammography with BIRADS. Descriptive statistical analysis. X2 test and Cramer correlation with confidence level of 95%. Results: 44 cases were analyzed. The average age of women was 52.04 ± años (IC 95%: 40.9 - 63.2). Predominant group of 56 to 70 years, 47.7 % (IC 95%: 36.5-58.9). Diagnosis with breast cancer 22.7% (IC 95%: 13.3 - 32.1), BI-RADS 2 in 4.5% (IC 95%: 0 - 9.1), BIRADS 3 in 29.5% (IC 95%: 19.3 - 39.7), BI-RADS 4 in 56.9% (IC 95%: 45.8 - 68.0) BI-RADS 5 in 9.1% (IC 95%: 2.7 - 15.5). The correlation between mammography and histopathological diagnosis was 0.26, p = 0.43. Conclusions: There was a low, no significant correlation, likely to include women with BI-RADS in early stage.